Proposal of diagnostic method for distribution network - Kowalski, Dariusz; Suchorab, Paweł (Instal, 2021)
The aim of this paper is to present the detecting abnormal conditions system, including its concepts and effects after 3-month period operation. The analysed water supply system, of total pipe length equal to approx. 260 km, consists of 24 pressure zones, 7 water tanks and 15 water pumping stations. The essence of the system is the integration of numerical model (developed in Bentley WaterGems software) and SCADA monitoring system. The monitoring data are constantly compared to simulation results and when accepted compliance limits are exceeded the appropriate alerts are generated. Such solution cause that the WSS operator does not need to analyse SCADA system indications constantly. The additional application of the system enables the detection of water leakages.
Keywords: water network; numerical model; failures; diagnostic method